Kepastian Hukum Akta Otentik yang Dibuat oleh Notaris di Luar Wilayah Jabatannya - Putri, Reni Anita; Setiadi, Yuliana; Kumala, Yudha Cahya (Universitas Muhammadiyah Kotabumi, 2025)
An authentic deed is the highest legal evidence in the civil evidence system made by a public official, namely a notary, who acts in accordance with his/her area of ​​office. Problems arise when a notary exercises his/her authority outside the area stipulated in his/her appointment letter, which is normatively prohibited by Article 17 paragraph (1) letter a of the Notary Law. This study aims to analyze the form of legal responsibility of a notary and the implications of legal certainty for deeds made outside the area of ​​office. By using normative legal methods and statutory, conceptual, and case study approaches, it was found that deeds made outside the area of ​​office lose their authentic nature and only have the power as private deeds. Notaries who violate these provisions can be subject to administrative, civil, and even criminal sanctions. This creates legal uncertainty for the parties interested in the deed and disrupts public trust in the notary profession. Therefore, compliance with the boundaries of the area of ​​office is an absolute requirement for the formal and substantial validity of an authentic deed.